1977
DOI: 10.1007/bf00508619
|View full text |Cite
|
Sign up to set email alerts
|

Increase of serum very low density lipoproteins in rats after administration of ?-hexachlorocyclohexane

Abstract: After enteral administration of 200 mg/kg alpha-hexachlorocyclohexane (alpha-HCH) female Wistar rats develop a hyperlipemia. 48 h after administration of alpha-HCH, serum triglycerides are increased by 300%, whereas both serum cholesterol and serum total phospholipids only increase by about 45%. Serum free fatty acids are not significantly altered. Fractionation of the serum lipoproteins by ultracentrifugation shows that the hyperlipemia is due to a fivefold increase in serum very low density lipoproteins. Hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

1978
1978
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Furthermore, within the family of membrane proteins, the expression of low-density lipoprotein receptor (LDL receptor) was reduced in α - HCH–treated rat liver slices. This is in keeping with findings that female Wistar rats that had been given α -HCH develop a hyperlipemia, due to an increase in serum very-low-density lipoprotein (Grajewski and Oberdisse 1977). Regarding signal transduction, the expression of both of the mitogen-activated protein (MAP) kinase family members ERK2 and ERK3 was changed, ERK3 being increased and ERK2 repressed.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, within the family of membrane proteins, the expression of low-density lipoprotein receptor (LDL receptor) was reduced in α - HCH–treated rat liver slices. This is in keeping with findings that female Wistar rats that had been given α -HCH develop a hyperlipemia, due to an increase in serum very-low-density lipoprotein (Grajewski and Oberdisse 1977). Regarding signal transduction, the expression of both of the mitogen-activated protein (MAP) kinase family members ERK2 and ERK3 was changed, ERK3 being increased and ERK2 repressed.…”
Section: Discussionsupporting
confidence: 90%
“…Grajewski et al reported that female Wistar rats developed hyperlipemia after enteral administration of 200 mg/kg alpha-HCH and serum triglycerides were increased by 300% at 48 h after administration, with increased hepatic very low density lipoptotein (VLDL) secretion (Grajewski and Oberdisse, 1977). Both serum cholesterol and serum total phospholipids were also increased by about 45%, whereas serum free fatty acids were not significantly altered.…”
Section: Discussionmentioning
confidence: 99%
“…In the bile acid pathway, cholesterol serves as a substrate that is converted to bile acids through the activation of 7-α-hydroxylase, the transcript for which is also significantly elevated in obese mice. Lastly, studies show that γ-hexachlorocyclohexane administration has been shown to increase serum cholesterol and very low-density lipoprotein (VLDL) levels [24]. Several genes occur multiple times in these 13 pathways (for example, the aldehyde dehydrogenase gene family ( Aldh1a1 , Aldh2 , and Aldh3a2 )).…”
Section: Discussionmentioning
confidence: 99%